Public Stigma Toward HIV/AIDS in Pulo Brayan Darat I Village, Medan Timur District - Yuni Shanti Ritonga; Aini Fadillah (Benih : Journal of Midwifery, 2026)
Social stigma towards people living with HIV/AIDS (PLWHA) remains a major challenge in HIV/AIDS prevention and management efforts in Indonesia. This study aims to evaluate social stigma in Pulo Brayan Darat I Village, Medan Timur District, and identify the factors that influence it. The study used a qualitative approach with a descriptive phenomenological design. Data were collected through in-depth interviews with eight informants selected using purposive sampling, supplemented by observation and documentation. The results of the study found that public understanding of HIV/AIDS is still low, especially regarding its transmission, which causes stigma and fear towards PLWHA. The community considers HIV to be a deadly and easily transmitted disease, so they tend to keep their distance and discriminate, although some have begun to show an inclusive attitude towards the rights of PLHIV to work and socialize. The conclusion of this study shows that low levels of knowledge are a major factor in the emergence of stigma and discrimination, so continuous education is needed to improve social acceptance and improve the quality of life of PLHIV.